2015
DOI: 10.1177/2150135115589790
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Sternal Cleft in a Patient With Coronary Artery Disease

Abstract: A cleft sternum is a very rare developmental anomaly. It is caused by failure of fusion of the two lateral mesodermal sternal bars which later form the sternum. Diagnosis of cleft sternum is generally made in the neonatal period, and it is usually associated with other congenital defects. Occasionally, patients with cleft sternum may be reported late in the childhood or even in adulthood. We present the case of an adult patient with sternal cleft diagnosed incidentally in the perioperative period at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Comment. The sternal cleft is a rare congenital malformation: only about 100 cases have been previously reported in the literature [1]. Among numerous classification schemes have been described we found that the most accurate and applicable for our case was proposed by Fokin et al [2].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Comment. The sternal cleft is a rare congenital malformation: only about 100 cases have been previously reported in the literature [1]. Among numerous classification schemes have been described we found that the most accurate and applicable for our case was proposed by Fokin et al [2].…”
mentioning
confidence: 60%
“…
Вроджені вади серцяIntroduction. Sternal cleft (SC) is a rare congenital abnormality which accounts for 0.15% of chest wall malformations [1]. The two lateral mesodermal sternal bars have to be fused by the eighth week of gestation but in patients with SC this process is broken.
…”
mentioning
confidence: 99%
“…Furthermore, the complication and mortality rates of the surgery are low 10 . Therefore, regardless of symptoms, surgical correction of congenital cleft sternum should be performed during the neonatal period 4,11,12,15 . It achieves direct closure with a satisfactory cosmetic effect 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it typically does not disrupt. 2 In addition, this abnormality more commonly affects female individuals, 1,4,9,[11][12][13] who comprise approximately 75% of patients. 14 Although sternal embryology has been carefully studied, the etiology of this defect remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation